Scalable Coding Of Motion And Depth Fields With Shared Breakpoints - Mathew, R.; Li, Y.; Taubman, D. (Proceedings - International Conference on Image Processing, 2021)
A new breakpoint adaptive DWT, referred to as tri-break, is currently being considered by standardization efforts in relation to JPEG 2000 Part 17 extensions. We first provide a summary of the tri-break transform and then explore its performance for coding motion fields. Experimental results show that significant gains can be achieved for coding piecewise smooth motion flows by employing the tri-break transform. We demonstrate the feasibility of utilising a common set of breakpoints for compressing depth maps and motion fields anchored at the same frame. We also extend prior work to decode motion vector fields directly onto a triangular mesh, enabling operations such as view warping to be defined on triangular cells which can be efficiently processed by GPU based architectures.